Mitigating fire sales with a central clearing counterparty - Vuillemey, Guillaume (Journal of Financial Intermediation, 2023)
Theoretically, one rationale for central clearing counterparties is the mitigation of inefficiencies associated with distressed asset sales. With novel archival data, I empirically study the first event in economic history during which a CCP successfully played this role: the global wool crisis of 1900. In the leading wool futures market in France, an inefficient equilibrium with fire sales and cascading defaults could be avoided due to price support provided by surviving CCP members. Cooperation to achieve price support–which is nowadays the main element of CCP auctions–could arise due to family relationships and cultural proximity between traders.